Addressing the impacts of climate change : focus on the Caribbean (ECLAC [Port of Spain]TT, 2007)
Defines climate change and identifies the drivers of climate change. Looks at climate trends in the Caribbean region and its impacts. Examines the response to climate change. Suggests the way forward for the Caribbean region.
Keywords: CLIMATE CHANGE